SEBARAN DAN STATUS BEKANTAN (Nasalis larvatus) DI KABUPATEN TANAH BUMBU, KALIMANTAN SELATAN - Soendjoto, Mochamad Arief; Sundari, Titik; Budiarto, Cecep; Muhardiansyah, Hafizh (Universitas Sebelas Maret, 2014)
The proboscis monkey (Nasalis larvatus) is the fauna mascot of Kalimantan Selatan Province. Distribution and its status inTanah BumbuRegency had not been reported yet. The objectives of the research were to document locationswhere the proboscis monkey lives in, estimate their population, and identifythe factorsinfluencingthe population. Methodsapplied were interview the people and directly survey to the field. The monkeys were found in 15 of 19 locations surveyed andthe population was more than 245 individuals, but they were not in 4 others. In addition to galam forest, mangrove forest, swamp forest, riverine forest, rubber forest, and forest growing on the limestone hill, the proboscis monkeys were found living in lands of ex-cultivation (ex-ladang), ex-fishpond, andex-sawmill industry. The factorsinfluencing or being likely to decrease the population were the broadening of oil-palm plantationand the development ofcoal mining, coal harbors, illegal logging, land/forest fire, and ressettlements.Â Key Words: location, Nasalis larvatus, population, status, Tanah Bumbu